Cancer-related fatigue in patients undergoing hematopoietic stem cell transplant: a cross-sectional study on prevalence and influencing factors - Wu, Xia; Xu, Qiufang (Frontiers in Psychiatry, 2025)
BackgroundFatigue constitutes a highly prevalent symptom within the cancer patient population, exerting a profound and multifaceted impact on their quality of life. Within the specific context of hematopoietic stem cell transplantation (HSCT), a therapeutic modality associated with significant physiological and psychological stressors, the manifestation and determinants of fatigue remain inadequately characterized. The present study was therefore designed to systematically assess the prevalence of fatigue among HSCT recipients and identify key factors influencing its occurrence.MethodsThis cross-sectional study encompassed HSCT recipients treated at our hospital from November 2023 to November 2024. Fatigue levels were assessed using the Revised Piper Fatigue Scale. Data were collected during outpatient follow-up visits, which occurred at least 1 month after HSCT to ensure stabilization of physical and psychological status.ResultsA total of 214 HSCT recipients were enrolled in the analysis. Among them, 88 patients reported fatigue, yielding a prevalence rate of 41.12%. Bivariate correlation analysis revealed statistically significant associations between fatigue and four variables: age (r = 0.530), gender (r = 0.509), per capita monthly household income (r = 0.552), and number of transplantation attempts (r = 0.602), with all correlation coefficients reaching significance at p < 0.05. Further logistic regression analysis confirmed these variables as independent associated factors of fatigue in HSCT recipients: age (OR = 2.410, 95% CI: 2.015–3.104), gender (OR = 2.504, 95% CI: 2.113–2.866), per capita monthly household income (OR = 3.218, 95% CI: 2.830–3.885), and number of transplantation attempts (OR = 3.652, 95% CI: 2.965–4.124), with all predictors demonstrating statistical significance at p < 0.05.ConclusionHSCT recipients exhibit a high prevalence of fatigue, with emotional and sensory dimensions emerging as its primary characteristics. These findings underscore the imperative for healthcare practitioners to design and execute targeted interventions grounded in the identified risk factors, thereby effectively alleviating fatigue in this patient population.